2012
DOI: 10.1084/jem.20120994
|View full text |Cite
|
Sign up to set email alerts
|

The origins, function, and regulation of T follicular helper cells

Abstract: The generation of high-affinity antibodies (Abs) plays a critical role in the neutralization and clearance of pathogens and subsequent host survival after natural infection with a variety of microorganisms. Most currently available vaccines rely on the induction of long-lived protective humoral immune responses by memory B cells and plasma cells, underscoring the importance of Abs in host protection. Ab responses against most antigens (Ags) require interactions between B cells and CD4+ T helper cells, and it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
468
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(485 citation statements)
references
References 108 publications
(356 reference statements)
9
468
0
8
Order By: Relevance
“…Patients with pSS have elevated proportions of circulating T follicular helper (cTfh) cells, defined as CXCR5 + PD-1 + CD45RA − CD4 + cells, compared with healthy controls [17,33,34]. The B cell hyperactivity that is present in pSS patients may favor differentiation of Tfh cells through secretion of IL-6 by activated B cells in conjunction with high expression of costimulatory molecules (e.g., CD40, ICOS-L) [35,36]. Tfh cells subsequently activate B cells and promote germinal center formation and plasma cell formation [36], providing a positive-feedback loop.…”
Section: Effects Of Rituximab On the Cd4 + T Cell Compartmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with pSS have elevated proportions of circulating T follicular helper (cTfh) cells, defined as CXCR5 + PD-1 + CD45RA − CD4 + cells, compared with healthy controls [17,33,34]. The B cell hyperactivity that is present in pSS patients may favor differentiation of Tfh cells through secretion of IL-6 by activated B cells in conjunction with high expression of costimulatory molecules (e.g., CD40, ICOS-L) [35,36]. Tfh cells subsequently activate B cells and promote germinal center formation and plasma cell formation [36], providing a positive-feedback loop.…”
Section: Effects Of Rituximab On the Cd4 + T Cell Compartmentmentioning
confidence: 99%
“…The B cell hyperactivity that is present in pSS patients may favor differentiation of Tfh cells through secretion of IL-6 by activated B cells in conjunction with high expression of costimulatory molecules (e.g., CD40, ICOS-L) [35,36]. Tfh cells subsequently activate B cells and promote germinal center formation and plasma cell formation [36], providing a positive-feedback loop. We have recently shown that cTfh cells, and to a smaller extent also Th17 cells, are reduced by rituximab [17].…”
Section: Effects Of Rituximab On the Cd4 + T Cell Compartmentmentioning
confidence: 99%
“…cluster of differentiation (CD)40L and signaling lymphocytic activation molecule (SLAM)-associated protein (SAP) which are critical in T-B cell interaction [9,[12][13][14][15][16]. In the follicles, [20].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This leads to Ag internalization, presentation of the processed Ag peptides into MHC class II (MHC II) molecules, and migration of the activated B cells to the border of the T-B-cell zone [4]. T FH cells are induced in the T-cell zone by dendritic cells (DCs) that have internalized and present peptides of the same Ags [6]. T FH -cell differentiation requires upregulation of the transcriptional repressor B-cell lymphoma-6 (BCL-6) and costimulation with CD28 and interleukin-21 (IL-21) [6], and results in the upregulation of CXC chemokine receptor 5 (CXCR5), iNKT cells iNKT cells are a unique T-cell subset characterized by the expression of a conserved invariant T-cell receptor (TCR) Vα chain (Vα14Jα18 in mice; Vα24Jα18 in humans), paired with a restricted repertoire of diverse TCR Vβ chains (Vβ8.2, Vβ7, or Vβ2 in mice; Vβ11 in humans) [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…T FH cells are induced in the T-cell zone by dendritic cells (DCs) that have internalized and present peptides of the same Ags [6]. T FH -cell differentiation requires upregulation of the transcriptional repressor B-cell lymphoma-6 (BCL-6) and costimulation with CD28 and interleukin-21 (IL-21) [6], and results in the upregulation of CXC chemokine receptor 5 (CXCR5), iNKT cells iNKT cells are a unique T-cell subset characterized by the expression of a conserved invariant T-cell receptor (TCR) Vα chain (Vα14Jα18 in mice; Vα24Jα18 in humans), paired with a restricted repertoire of diverse TCR Vβ chains (Vβ8.2, Vβ7, or Vβ2 in mice; Vβ11 in humans) [12,13]. The semi-invariant TCR recognizes CD1d [14], a member of the CD1 family of nonpolymorphic, MHC-I-like lipid Ag presenting molecules that is expressed on monocytes, DCs, B cells, and some nonhematopoietic cells (reviewed in [15]).…”
mentioning
confidence: 99%